MODEL OF ECONOMIC PARTNERSHIP IN THE NETWORK ECONOMY - KUKURUDZ, Rostyslav (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Significant changes in the development of new interdependencies between companies, the development of the value chain concept, and technological progress in the field of electronic communications between companies are the main prerequisites for the significant interest of theorists in network structures. Some scholars believe that the study of two-way relationships reflects the popularity of the concept of affiliate marketing, while the focus on networks is a higher level of marketing development. Given that the achievement of long-term cooperative trade relations primarily depends on the will and capacity of both partner parties (bilateral control), it is clear that their nature can be explored in more detail only through mutual considerations. Significant changes in the development of new interdependencies between companies, the development of the value chain concept, and technological progress in the field of electronic communications between companies are the main prerequisites for the significant interest of theorists in network structures. Some scholars believe that the study of two-way relationships reflects the popularity of the concept of affiliate marketing, while the focus on networks is a higher level of marketing development. Given that the achievement of long-term cooperative trade relations primarily depends on the will and capacity of both partner parties (bilateral control), it is clear that their nature can be explored in more detail only through mutual considerations.
Keywords: model; merging economy; company; merging structure